Experiences of establishing an academic early phase clinical trials unit. (August 2017) - Brown, Sarah R; Sherratt, Debbie; Booth, Gill; Brown, Julia; Collinson, Fiona; Gregory, Walter; Flanagan, Louise
Background: Early phase trials are essential in drug development, determining appropriate dose levels and assessing preliminary activity. These trials are undertaken by industry and academia, with increasing collaborations between the two. There is pressure to perform these trials quickly, safely, and robustly. However, there are inherent differences between developing and managing early phase, compared to late phase, drug trials. This article describes an approach to establishing an academically led early phase trial portfolio, highlighting lessons learned and sharing experiences. Methods: In 2009, the University of Leeds Clinical Trials Research Unit became the Clinical Trials Coordinating Office for Myeloma UK's phase I and II trials. We embarked on a transition from working extensively in phase III to early phase trials development and conduct. This involved evaluating and revising our well-established standard operating procedures, visiting other academic early phase units, and developing essential new documentation and processes. Results: A core team of trial and data managers and statisticians was established to facilitate expertise and knowledge retention. A detailed training plan was implemented focussing on essential standard practices for early phase. These included pharmacovigilance, recruitment, trial design and set-up, data and site monitoring, and oversight committees. Training in statistical methods for early phase trials was incorporated. Conclusion: Initial scoping of early phase trial management and conduct was essential in establishing this early phase portfolio. Many of the processes developed were successful. However, regular review and evaluation were implemented to enable changes and ensure efficiencies. It is recommended that others embarking on this venture build on the experiences described in this article.